Study on the trend of congenital heart disease inpatient costs and its influencing factors in economically underdeveloped areas of China, 2015–2020: a case study of Gansu Province - Zhou, Shengze; Yang, Yaya; Wang, Lei; Liu, Heming; Wang, Xuemei; Ouyang, Changping; Pan, Jinhua; Hu, Xiaobin (Frontiers in Public Health, 2024)
Background: Economic data on congenital heart disease are scarce in economically underdeveloped areas of China. Therefore, this study aimed to shed light on the level and changing trend of congenital heart disease inpatients' economic burden in underdeveloped areas.This study used a multi-stage stratified cluster sampling method to select 11,055 inpatients with congenital heart disease from 197 medical and health institutions in Gansu Province. Their medical records and expenses were obtained from the Hospital Information System. Univariate analysis was conducted using the rank sum test and Spearman rank correlation. Quantile regression and random forest were used to analyze the influencing factors.Results: From 2015 to 2020, the average length of stay for congenital heart disease patients in Gansu Province was 10.09 days, with an average inpatient cost of USD3,274.57. During this period, the average inpatient costs per time increased from USD3,214.85 to USD3,403.41, while the average daily inpatient costs increased from USD330.05 to USD376.56. The average out-of-pocket costs per time decreased from USD2,305.96 to USD754.77. The main factors that affected the inpatient costs included length of stay, cardiac procedure, proportion of medications, age, and hospital level.批注 [sz1]: Many thanks to the editors and reviewers for your careful comments and questions about this manuscript! The resubmitted manuscript has been corrected for the issues you pointed out and marked in the manuscript with different colors. This is shown as Reviewer #2 comments -yellow, Reviewer #3 commentsgreen, please do a second review and comment. Thanks again for all your hard work! Conclusion: Congenital heart disease causes a significant economic burden on both families and society. Therefore, to further reduce the patient's financial burden, the length of stay should be reasonably reduced, and the rational distribution of medical resources should be continuously promoted to ensure equitable access to healthcare services.